Errand into the wilderness of mirrors : religion and the history of the CIA - Graziano, Michael (Religion scholar) (Chicago; London: University of Chicago Press, 2021)
"Michael Graziano investigates the religious conceptions of those who shaped and worked for the CIA, arguing that the Catholicism of key CIA figures--such as "Wild" Bill Donovan and Edward Lansdale--was decisive in establishing the agency's concerns, methods, and understandings of the world. In part this was because the Roman Catholic Church already had global networks of people and safe places that American agents could use to their advantage. But conversely, American agents were overly inclined to view other powerful religions and religious figures in the same framework as Catholicism--misconceptions that led, too often, to tragedy and disaster"--
Introduction : charting the wilderness -- American spies and American Catholics -- Refining the religious approach -- The great jihad of freedom -- On caring what it is -- Baptizing Vietnam -- Counterinsurgency and the study of world religions -- Iran and revolutionary thinking -- Conclusion : a new wilderness.
Includes bibliographical references and index.
Keywords: United States. -- Central Intelligence Agency -- History; United States. -- Office of Strategic Services -- History; United States. -- Central Intelligence Agency -- Religion; United States. -- Office of Strategic Services -- Religion; National security -- United States -- Religious aspects; Intelligence service -- United States -- History -- 20th century; Intelligence officers -- United States; Cold War -- Religious aspects